Protein Levels of Pro-Inflammatory Cytokines and Chemokines as Biomarkers of Mycobacterium bovis Infection and BCG Vaccination in Cattle - Hamza Khalid; Anouk van Hooij; Timothy K. Connelley; Annemieke Geluk; Jayne C. Hope (Pathogens, 2022)
Bovine tuberculosis (bTB), caused by Mycobacterium bovis, is a globally prevalent infectious disease with significant animal welfare and economic impact. Difficulties in implementing test-and-slaughter measures in low- and middle-income countries (LMICs) and the underperformance of the current diagnostics establish a clear need to develop improved diagnostics. Adaptive immunity biomarkers other than IFNγ could be useful as suggested by various gene expression studies; however, a comprehensive assessment at the protein level is lacking. Here, we screened a range of chemokines and cytokines for their potential as biomarkers in samples from M. bovis experimentally challenged or naive animals. Although serum concentrations for most proteins were low, the pro-inflammatory markers, IL-2, CXCL-9, IP-10 and CCL4, in addition to IFNγ, were found to be significantly elevated in bovine tuberculin (PPDb)-stimulated whole blood supernatants. Further assessment of these molecules in BCG-vaccinated with or without subsequent M. bovis challenge or naive animals revealed that PPDb-specific IL-2 and IP-10, in addition to IFNγ, could discriminate naive and BCG-vaccinated from M. bovis challenged animals. Moreover, these proteins, along with CCL4, showed DIVA potential, i.e., enabling differentiation of M. bovis-infected animals from BCG-vaccinated animals. Combined analysis of cytokines and chemokines could also accurately identify M. bovis infection with strong correlations observed between PPDb-specific IFNγ, IL-2 and IP-10 levels. This provides proof of concept for utilizing multiple biomarker signatures for discrimination of animals with respect to M. bovis infection or BCG vaccination status.